New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part IV. Genera Eugnoriste Coquillett and Keilbachia Mohrig - Mohrig, Werner; Kauschke, Ellen (Zootaxa, 2017)
In the Nearctic region the genus Eugnoriste includes 7 species currently. Four of them are new to science. These are Eugnoriste brachycostalis sp. n., Eug. florea sp. n., Eug. hirsuta sp. n. and Eug. ptilosis sp. n. The male of Eug. brevirostris Coquillett, which has been unknown until now, was identified and described herein. Moreover, an additional description and figures were given for Eug. occidentalis Coquillett. Eugnoriste villosoabdominalis Mohrig is reported as new for North America. The genus Keilbachia includes three species in the Nearctic region presently. Two of them are new to science. These are Keilbachia americana sp. n. and K. semiacuta sp. n. All species presented here were diagnosed, keyed and illustrated by figures as well as data of their distribution provided.